Impacts of e-business, e-negotiation, and trust building on e-agribusiness performance: a preliminary study on MBA students of Universiti Utara Malaysia / Assem O. Ali Mmar and Abdul Manaf Bohari - Mmar, Assem O. Ali; Bohari, Abdul Manaf (Universiti Teknologi MARA, Perlis, 2011)
The main purpose of this study is to investigate the impacts of e-business, e-negotiation and trust building specifically on online e-agribusiness performance. The existing trend of online base e-agribusiness has rise some implication on current and future performance among agribusiness firms especially on the big potential of e-business and e-negotiation to agribusiness sectors. This preliminary study was conducted among fifty Master of Business Administration (MBA) students in University Utara Malaysia where all of them are familiar with agribusiness sector. The finding obtained from this study indicated that there was a significant (2 tailed significant) relationship between independent variables (e-business, e-negotiation, and trust building) and dependent variable (e-agribusiness performance). In sum, the result obtained from this study indicated that four hypotheses tested in this study were accepted.